(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
The excitation of terahertz (THz) surface plasmons by a density modulated relativistic electron beam propagating in a parallel plane semiconducting structure is investigated. The interaction of the electromagnetic surface wave with density modulated electron beam in the guiding structure is examined in the present work, which shows a significant enhancement in the radiation wave. The growth rate of the instability increases linearly with modulation index and reaches the largest value when the phase matching condition is satisfied in the generation of THz radiation wave, i.e., when the phase velocity of the THz radiation wave is comparable to the velocity of modulated beam. In addition, the growth rate of instability scales as one-third power of beam current and modulation index. Moreover,the surface plasmons resonance can be tuned in THz frequency range by the conventional doping concentration of the semiconductors.